An AI-Assisted Systematic Review of Biology Learning Strategies for Sustainability - Husamah, H.; Rahardjanto, Abdulkadir; Permana, Tutut Indria; Shukri, Ahmad Adnan Mohd (Journal of Natural Sciences, 2025)
This study aims to uncover key strategies in biology learning that support sustainability through a Scopus AI–assisted literature review. Using a qualitative review approach combined with clustering and concept mapping techniques, 68 Scopus-indexed journal articles published between 2015 and 2025 were analyzed. Searches employed both natural language and Boolean keyword queries: (“biology” OR “life science”) AND (“education” OR “learning”) AND (“sustainability” OR “environmental”). Conceptual synthesis revealed three interrelated domains, Environmental Awareness, Student-centered Pedagogies, and Sustainability Education, each encompassing strategies such as experiential and problem-based learning, SDG-integrated modules, biomimicry-based innovation, and community engagement. These findings indicate that biology learning for sustainability extends beyond content mastery toward transformative pedagogy and ecological ethics, positioning biology as a platform for cultivating ecological citizenship. However, the study is limited by its reliance on Scopus AI metadata and abstracts, which may not fully capture methodological nuances and contextual depth of the original studies.